2021
DOI: 10.1021/acsami.1c06391
|View full text |Cite
|
Sign up to set email alerts
|

Pillared Metal–Organic Framework Initiating Intermolecular Atom-Transfer Radical Addition via Visible-Light-Induced Electron Transfer Activation of Haloalkanes

Abstract: Herein, a novel metal–organic framework (MOF) with a pillared-layer structure was rationally synthesized to initiate intermolecular atom-transfer radical addition (ATRA) via photoinduced electron transfer activation of haloalkanes. The MOF synthesized via the controllable pillared-layer method is of excellent visible-light absorption and high chemical stability. Photocatalytic experiments show the atom transfer of various alkyl halides (R–X, X = Cl/Br/I) onto diverse olefins was successfully achieved to produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Thereafter, the tolerance of olefin substrates was studied using a series of olefins with different substituents. As shown in Table 2, styrene with halide [F (11), Cl (12), and Br (13)] and methoxy groups ( 14) and terminal alkenes with alkyl substituents such as cyclohexyl (15), ethylbenzene (16), ester groups (17), and benzyl ( 18) are all available coupling partners, showing good yields of 65−99%. In addition, cyclohexene was also demonstrated to be effective for the reaction (19, 64%).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, the tolerance of olefin substrates was studied using a series of olefins with different substituents. As shown in Table 2, styrene with halide [F (11), Cl (12), and Br (13)] and methoxy groups ( 14) and terminal alkenes with alkyl substituents such as cyclohexyl (15), ethylbenzene (16), ester groups (17), and benzyl ( 18) are all available coupling partners, showing good yields of 65−99%. In addition, cyclohexene was also demonstrated to be effective for the reaction (19, 64%).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Coordination polymers (CPs) are a kind of hybrid material constructed by the coordination interaction between inorganic metal ions/clusters and organic linkers. , Due to the synthetic feasibility and rich diversity of inorganic/organic building units, a number of visible-light-responsive CPs have been designed and synthesized for photocatalytic reactions. Successful studies have shown these materials are promising photocatalysts for desirable chemical transformations, such as the photoreduction of carbon dioxide, degradation of aqueous pollutants, and water splitting. In particular, the use of photoactive CPs for organic transformation is highly intriguing, though it is still in the very early stages. Currently, the field of visible-light-mediated photoredox chemistry of organic synthesis is growing vigorously due to its unique reactivity, mild reaction conditions, and easy operation setup in response to the demand for green and environmentally friendly chemistry. However, the study relies heavily on the use of a few kinds of homogeneous photocatalysts such as Ir/Ru complexes. , The application of photoactive CPs for organic transformation would greatly supplement the current photoredox studies using metal complexes, considering that CPs show different charge photogeneration and photocatalytic activities compared to those of the homogeneous metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In the last dozen years, MOF-based photocatalysts have been extensively developed due to their high porosities and structural tailorabilities. They play an important role in CO 2 photoreduction, H 2 O splitting, pollutant degradation, and a large variety of organic synthesis. , MOFs containing BINOL derivative ligands are also widely used in thermal catalysis, luminescent materials, adsorption, and separation, but their potential as photocatalysts is still undeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] More importantly, the photophysical properties of MOFs can be conveniently regulated at the molecular level with the help of abundant inorganic and organic building blocks. [16][17][18] In recent years, MOFs as heterogeneous catalysts have made notable progress in photoreduction of CO 2 to high added-value products. [19][20][21][22][23][24] Considering the commercialization of MOF catalysts, a great deal of efforts have been devoted to developing MOF catalysts with high stability, broad light absorption and abundant multiple active sites.…”
Section: Introductionmentioning
confidence: 99%